Yasin Recitation to the Late Haji Abd Rahman Ayub, Father of YBhg. Prof. Ts. Dr Norazah Abd Rahman - UiTM, Pejabat Timbalan Naib Canselor (Penyelidikan & Inovasi) (UiTM, 2024)
News and activities Office of Deputy Vice-Chancellor (Research & Innovation) Jan 2024.